Numerical Study on the Effect of Geometrical Parameters on the Performance of Vortex Tube Cooling Device Using Simflow - Mohd Hazwan, Yusof; Muhammad Fadhli, Suhaimi; Mohd Hilmi, Mohd Aris; Syed Mohammad, Akhtar (2016)
Vortex tube is a simple device which can separate room temperature compressed gas into the cold and hot flow. The performance of vortex tube is mainly affected by its geometrical parameters. In this study, the parameters are focused on cold outlet diameter and hot tube length. The objective of this study is to investigate the effect the cold outlet diameter and hot tube length in the range of 4-5 mm and 175-194 mm, respectively, when the inner diameter of vortex tube is 10 mm. The numerical investigation was carried using SIMFLOW 2.1 to predict the performance of vortex tube. The results show that 4 mm cold outlet diameter and 175 mm hot tube length is the optimum parameter for 10 mm inner tube diameter of the vortex tube.